Monitoring & evaluating climate change adaptation at local and regional levels : learning from international experience to develop an M&E methodology (French Environment and Energy Management Agency (ADEME) CedexFR, 2013)
Presents a resource guide based on international experience to aid in the development of an M & E methodology. Adapts practices to the needs of local authorities in France working on territorial climate and energy plans.
Keywords: CLIMATE CHANGE